Evaluation of an Incorporated Superior Capsular Reconstruction Graft: A Case Report. Issue 3 (July 2019) - Samade, Richard; Jones, Grant L.; Bishop, Julie Y.
Abstract : Case: A 66-year-old man presented with 2 years of atraumatic right shoulder pain and difficulty with overhead activities. Radiographs and magnetic resonance imaging demonstrated Hamada stage I changes and a massive irreparable rotator cuff tear involving the supraspinatus and infraspinatus. He underwent superior capsular reconstruction with acellular human dermal matrix (SCR with ADM) allograft. Diagnostic arthroscopy and humeral avulsion of the glenohumeral ligament repair 1 year postoperatively showed that the SCR appeared intact and vascularized. Conclusions: This is the first study to confirm visually that SCR with ADM allograft is well-vascularized and intact 1 year post-operatively.